Understanding the Structure and Energy Transfer Process of Undoped Ultrathin Emitting Nanolayers Within Interface Exciplexes - Xu, Ting; Fu, Jianhui; Wang, Xinzhong; Lu, Guanhua; Liu, Baiquan (Frontiers in Chemistry, 2022)
Organic light-emitting diodes (OLEDs) have great potential for display, lighting, and near-infrared (NIR) applications due to their outstanding advantages such as high efficiency, low power consumption, and flexibility. Recently, it has been found that the ultrathin emitting nanolayer technology plays a key role in OLEDs with simplified structures through the undoped fabricated process, and exciplex-forming hosts can enhance the efficiency and stability of OLEDs. However, the elementary structure and mechanism of the energy transfer process of ultrathin emitting nanolayers within interface exciplexes are still unclear. Therefore, it is imminently needed to explore the origin of ultrathin emitting nanolayers and their energy process within exciplexes. Herein, the mechanism of films growing to set ultrathin emitting nanolayers (<1 nm) and their energy transfer process within interface exciplexes are reviewed and researched. The UEML phosphorescence dye plays a key role in determining the lifetime of excitons between exciplex and non-exciplex interfaces. The exciplex between TCTA and Bphen has longer lifetime decay than the non-exciplex between TCTA and TAPC, facilitating exciton harvesting. The findings will be beneficial not only to the further development of OLEDs but also to other related organic optoelectronic technologies.